Foreign Direct Investment in Nigerian Context: Conducive or Not? - Ubajaka, C (2009)
Foreign direct investment has been acknowledged to have a significant impact on the development of an economy, specifically developing countries like Nigeria. However, the problem does not lie with attracting these investments but sustaining it and marketing for potential ones. This research examines the hindrances faced by investors while drawing a link between FDI and growth. Data was obtained using a more direct approach of in-depth interviews, which attracts responses from eight individuals that cut across industries. From the feedback of responses, it was observed that the problems that are being faced in the economy revolved around similar issues of poor infrastructure, political instability, policy inconsistency e.t.c. but this is not something new. Therefore the research addresses policy issues that policy makers should consider more closely. Although economic growth is important, the most significant factor is the process of growth.And lastly, nigeria should act less dependent on the oil sector, so as to have a diversified portfolio for potential investors.